Presenting the Special Issue “Religions and cities.” - Araujo, Marcella (2024)
The dossier "Religions and Brazilian Cities, Crossed Paths" discusses multiple forms of the presence of religions in Brazilian cities. Here are gathered articles on various religious practices in cities of diverse sizes, formation histories, and regional locations.